The past, present, and future of the regulation of offshore chemicals in the North Sea—a United Kingdom perspective. (30th September 2019) - Sühring, R; Cousins, A; Gregory, L; Moran, C; Papachlimitzou, A; Phillips, C; Rowles, R; Supple, S; Wilczynska, M; Birchenough, S N R
Abstract: The North Sea is one of the most studied and exploited ecosystems worldwide. The multiple uses from industrial, transport, as well as recreational activities have required researchers, regulators, and legislators to understand and, where possible, to minimize any expected negative environmental impacts. As with any international sea, assessing the current pressures and management actions resulting from these activities is centred on several national and international legislative instruments. This variety of co-existing legislations makes development processes and regulatory assessments cumbersome and time consuming. Hence there is a need to integrate environmental risk assessment and management across sectors, ensuring smart, cost-effective data generation, as well as supporting and standardizing environmental practices. This paper provides an overview of the changing regulatory frameworks regarding offshore chemicals used in the oil and gas industry, and the process of chemical risk assessment conducted under the Offshore Chemical Notification Scheme (ONCS) in the UK. Our view of methodological, research, and regulatory needs and challenges that should be addressed to ensure an adequate and sustainable assessment of offshore chemical use in the North Sea is discussed. Furthermore, we discuss the issues faced regarding chemicals used in the UK oil and gas sector with respect to declining hydrocarbon production.